2001
DOI: 10.1097/00004647-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Ischemic Brain Injury in Cyclooxygenase-1–Deficient Mice

Abstract: Cyclooxygenase-1 (COX-1), a rate-limiting enzyme in the synthesis of prostanoids, is involved in selected vasodilatatory responses of the cerebral circulation. Cyclooxygenase-1-null mice were used to determine whether COX-1 influences cerebral ischemic damage. The middle cerebral artery was occluded in COX-1 -/- and +/+ mice (n = 9/group), and lesion volume was determined in thionin-stained sections 24 or 96 hours later. Middle cerebral artery occlusion produced larger infarcts in COX-1 -/- mice, both at 24 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 22 publications
(45 reference statements)
7
57
0
Order By: Relevance
“…In our stroke model, the infarct volume in vehicle-treated Cox1 À / À mice was similar as in Cox1 þ / þ animals in line with some but not all previous studies (Fig. 7c) [28][29][30] . Interestingly, nicotinic acid had no effect on the infarct volume in Cox1 À / À mice, whereas Cox1 þ / þ littermates were protected (Fig.…”
Section: Hca 2 Mediates the Neuroprotective Effect Of Ketogenic Dietsupporting
confidence: 91%
“…In our stroke model, the infarct volume in vehicle-treated Cox1 À / À mice was similar as in Cox1 þ / þ animals in line with some but not all previous studies (Fig. 7c) [28][29][30] . Interestingly, nicotinic acid had no effect on the infarct volume in Cox1 À / À mice, whereas Cox1 þ / þ littermates were protected (Fig.…”
Section: Hca 2 Mediates the Neuroprotective Effect Of Ketogenic Dietsupporting
confidence: 91%
“…COX-1 is constitutively expressed in many cells types, including microglia and leukocytes during brain injury . COX-1 deficient mice have increased vulnerability to brain ischemia, and would support a protective role possibly due to an effect on maintaining cerebral blood flow (Iadecola et al, 2001b). However, conflicting data exist.…”
Section: Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…First, it is quite clear that oxidative stress due to excessive levels of reactive oxygen species is a major mechanism of poststroke brain injury. Studies of stroke in mice either overexpressing antioxidants or deficient in pro-oxidant enzymes have reported smaller infarct volumes than in wild-type controls (Iadecola et al, 1997(Iadecola et al, , 2001Kinouchi et al, 1991;Sampei et al, 2000;WeisbrotLefkowitz et al, 1998;Yang et al, 1994), and conversely, studies of antioxidant-deficient mice have found larger infarcts (Crack et al, 2001;Kondo et al, 1997;Murakami et al, 1998). Moreover, several studies in Nox2-deficient mice have reported substantially smaller infarct and edema volumes, and less blood-brain barrier disruption than wild-type controls, pointing to Nox2 oxidase as a key source of damaging superoxide in the brain after stroke (Chen et al, 2009;Jackman et al, 2009;Kahles et al, 2007;Kunz et al, 2007;Walder et al, 1997).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%